Penguatan Nilai Empati pada Mahasiswa melalui Pembelajaran Berbasis Proyek - Kurniawati, Eni (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2026)
Empathy is an important character value that needs to be developed in students as part of personality formation and social responsibility. However, learning in higher education still tends to emphasize the cognitive aspect and does not provide enough space for strengthening the affective aspect, especially empathy. This study aims to describe the process and results of strengthening students' empathy values through the implementation of project-based learning. This study uses a qualitative approach with descriptive methods implemented for 6 months (1 semester). The subjects of the study were students of the Pancasila and Citizenship Education Study Program at Padang State University who participated in project-based learning with the theme of social sensitivity in society through real actions in the Values and Moral Education course. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used data reduction techniques, data presentation, and drawing conclusions. The results of the study indicate that project-based learning is able to strengthen students' empathy values, as seen from increased social sensitivity, the ability to understand others' perspectives, and a caring attitude towards community problems through real actions. These findings confirm that project-based learning is effectively used as a learning strategy to strengthen students' empathy values in higher education.